-5(u-6)=6u-3

Simple and best practice solution for -5(u-6)=6u-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(u-6)=6u-3 equation:


Simplifying
-5(u + -6) = 6u + -3

Reorder the terms:
-5(-6 + u) = 6u + -3
(-6 * -5 + u * -5) = 6u + -3
(30 + -5u) = 6u + -3

Reorder the terms:
30 + -5u = -3 + 6u

Solving
30 + -5u = -3 + 6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6u' to each side of the equation.
30 + -5u + -6u = -3 + 6u + -6u

Combine like terms: -5u + -6u = -11u
30 + -11u = -3 + 6u + -6u

Combine like terms: 6u + -6u = 0
30 + -11u = -3 + 0
30 + -11u = -3

Add '-30' to each side of the equation.
30 + -30 + -11u = -3 + -30

Combine like terms: 30 + -30 = 0
0 + -11u = -3 + -30
-11u = -3 + -30

Combine like terms: -3 + -30 = -33
-11u = -33

Divide each side by '-11'.
u = 3

Simplifying
u = 3

See similar equations:

| -x^2-16x+y-73=0 | | 7m-7=-42 | | 65.10+0.85x= | | 15=-5(x+20) | | Y=73+16x+x^2 | | 19s-18s+3s=20 | | 6x+3=3x+97 | | ln(x)+ln(x+8)=ln(9) | | 4.8x+3=27 | | 48=4x+12 | | 12m=-58+118 | | -20=2(u+5)-7u | | 24+3x=18 | | 13m=-64+129 | | R+5r-5r+R=18 | | 2x+7x^2=0 | | 26-9x=108 | | 1c+8p=35 | | 72-4x=12 | | (-7x-6)(x-5)+(8x-9)(5-x)= | | X+2=30-15 | | 2x-8x+1=9+10x | | 12+3a-5-8=2a+3 | | 3÷7/6 | | (-7x-6)(x-5)+(8x-9)= | | 17x/3=24 | | 14.95+13x=-15.00+.39x | | f/5-2=4 | | 5x-7x+6=12(x-3) | | 15=6-9n | | 5-3a=5(ya+2)-5 | | 7m+32=12-n |

Equations solver categories